Effects of adenoid/tonsillectomy on inflammatory response in snoring children with witnessed apnoea. (October 2014) - Mutlu, M.; Vuralkan, E.; Yardim Akaydin, S.; Akin, I.; Miser, E.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate the clinical significance of preoperative serum C‐reactive protein (CRP), interleukin‐6 (IL‐6), fetuin‐A, cystatin C, adiponectin and tumour necrosis factor‐alpha (TNF‐α) levels in children with adenoid/tonsillar hypertrophy and compare these results with postoperative values. Study design Prospective clinical trial. Setting Single tertiary care centre. Participants Thirty‐five children (14 boys and 21 girls) participated in this study. Main outcome measures The operations were performed with the indication of sleep‐disordered breathing (SDB). Blood samples were taken preoperatively and at 6 months postoperatively to determine the changes in serum high‐sensitivity CRP (hs‐CRP), IL‐6, fetuin‐A, cystatin C, adiponectin and TNF‐α levels. Pre‐ and postoperative values of body weights and heights of the participants were recorded preoperatively and at postoperative 6 months. Results Patients underwent adenoidectomy (n = 21) or adenotonsillectomy (n = 21). The mean age at surgery was 8.74 ± 3.33 years (range 3–16 years). Mean serum levels of parameters measured preoperatively and at postoperative 6 months. The observed differences between pre‐ and postoperative values were statistically significant (P < 0.05), excluding cystatin C levels (P > 0.05). Conclusion High levels of IL‐6, hs‐CRP and TNF‐α and low levels of fetuin‐A in serum might have a clinical significance in patients with sleep‐disordered breathing. Levels of cytokines in children with sleep‐disordered breathing because of adenotonsillar disease decreased after surgical treatment. The risks of development of cardiovascular disease are decreased in association with lower levels of cytokines, which are also closely associated with many disease states.